2004
DOI: 10.2135/cropsci2004.1839
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Growth Regulators on In Vitro Plant Regeneration in Durum Wheat

Abstract: Work on improvement of durum wheat (Triticum turgidum L.) using tools of biotechnology is limited. Development of a reliable in vitro plant regeneration procedure for this important cereal is a prerequisite for its improvement by genetic transformation. Here, we report the effects of three growth regulators (GRs), 2,4‐D (2,4‐dichlorophenoxyacetic acid), picloram (4‐amino‐3,5,6‐trichloropicolinic acid), and dicamba (3,6‐dichloro‐o‐anisic acid), on callus induction and plant regeneration from scutellum cultures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 46 publications
0
20
0
10
Order By: Relevance
“…Some authors reported a better response of Picloram compared to 2,4-D for induction and long-term maintenance of regenerative callus from immature embryo explants in barley (Kachhwaha et al1997), a species related to wheat, and durum wheat (Satyavathi et al 2004). Barro et al (1999) reported that in wheat the addition of Picloram (2 mg L -1 ) together with 2,4-D in culture medium increased plantlet regeneration by 50%.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors reported a better response of Picloram compared to 2,4-D for induction and long-term maintenance of regenerative callus from immature embryo explants in barley (Kachhwaha et al1997), a species related to wheat, and durum wheat (Satyavathi et al 2004). Barro et al (1999) reported that in wheat the addition of Picloram (2 mg L -1 ) together with 2,4-D in culture medium increased plantlet regeneration by 50%.…”
Section: Resultsmentioning
confidence: 99%
“…2,4-D was used successfully for callus induction in numerous experiments but this type of auxin at higher concentrations increases chromosomal instability and cause to somaclonal variation [31]. Therefore, in subsequent studies dicamba and picloram were used instead of 2,4-D [32]. In this study, two different synthetic auxins (2,4-D and picloram) in combination and alone were used for callus induction and somatic embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Efficient regeneration is usually observed on calli that originated from embryos or their parts [7,[11][12][13][14][15][16]. Histological studies have identified the scutellum of an immature embryo as the tissue from which embryogenic calli originate [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%